Interactive Multimedia Based on Problem-Based Learning to Improve Student Learning Outcomes in Science Subjects - Ni Made Dwi Meithayani; Gusti Ngurah Sastra Agustika; Komang Sujendra Diputra (Universitas Pendidikan Ganesha, 2025)
Low student learning motivation is one of the main factors contributing to poor academic achievement. This condition is further exacerbated by the use of conventional teaching methods without the support of engaging and interactive learning media. The purpose of this study is to analyze the effectiveness of interactive multimedia based on Problem-Based Learning for the topic “Types of Resistance” in the IPAS subject. This research is a development study. The development model used is the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The subjects of this study were 20 fourth-grade students. The methods and instruments used for data collection included interviews, observations, questionnaires, and multiple-choice tests. The data analysis techniques employed in this study were quantitative descriptive analysis, qualitative descriptive analysis, and inferential statistical analysis. The results showed that the calculated t-value (tcount = 11.203) was greater than the critical t-value (ttable = 1.71), indicating that H0 was rejected and H1 was accepted. Therefore, it can be concluded that interactive multimedia based on Problem-Based Learning is effective for teaching the topic “Types of Resistance” in the IPAS subject. This research can serve as a reference and motivation for teachers to utilize technology-based media and learning resources, thereby creating more varied and engaging learning experiences.